(untitled) (Community Based Medical Journal, 2022)
A cross-sectional, prospective study was conducted in a tertiary level eye hospital in the southern region of Bangladesh, between January and December of 2019, to assess the magnitude of blindness with varying disorders of the eye. All the reported patients irrespective of age and gender were included in this study. Patients were divided into three age groups: 0-25 years, 26-50 years and above 50 years. Demographic variables and eye diseases diagnosed were recorded and analyzed. More than 1.5 lac patients attended the hospital during the study period. Male patients were preponderance 79058 (52.05%) than female 72814 (47.95%). The most common group was above 50 years 75055 (49.42%). Patients related with blindness were 42189 (27.78%). Cataract were the most common disorder of reversible blindness 38662 (91.64%) followed by corneal disorders both reversible and irreversible blindness 1931 (4.57%), and other disorders 1596 (3.78%) with irreversible blindness included ocular trauma, posterior segment disease and glaucoma. Age related cataract (ARC) was 37394 (96.72%) among the patients with cataract, and ARC was found 35272 (83.6%) among the patients related to blindness above 50 years of age. More than 90 percent of the patients 38662 (91.64%) were attended for reversible blindness with cataract. To summarize, age related cataract was the most common cause of reversible blindness among the patients >50 years of age. The causes of irreversible blindness included ocular trauma, corneal ulcer, diabetic retinopathy and glaucoma. CBMJ 2021 January: vol. 10 no. 02 P: 70-74